Fault tolerant control of switched nonlinear systems with time delay under asynchronous switching - Xiang, Zhengrong; Wang, Ronghao; Chen, Qingwei (Zielona Góra: Uniwersytet Zielonogórski)
This paper investigates the problem of fault tolerant control of a class of uncertain switched nonlinear systems with time delay under asynchronous switching. The systems under consideration suffer from delayed switchings of the controller. First, a fault tolerant controller is proposed to guarantee exponentially stability of the switched systems with time delay. The dwell time approach is utilized for stability analysis and controller design. Then the proposed approach is extended to take into account switched time delay systems with Lipschitz nonlinearities and structured uncertainties. Finally, a numerical example is given to illustrate the effectiveness of the proposed method.
Keywords: time delay; fault tolerant control; switched nonlinear systems; asynchronous switching